Relative preservation of triceps over biceps strength in upper limb-onset ALS: the 'split elbow'. Issue 7 (7th March 2019) - Khalaf, Roaya; Martin, Sarah; Ellis, Cathy; Burman, Rachel; Sreedharan, Jemeen; Shaw, Christopher; Leigh, P Nigel; Turner, Martin R; Al-Chalabi, Ammar
Abstract : Objective: Amyotrophic lateral sclerosis (ALS) is a neurodegenerative disease of the motor system. The split hand sign in ALS refers to observed preferential weakness of the lateral hand muscles, which is unexplained. One possibility is larger cortical representation of the lateral hand compared with the medial. Biceps strength is usually preserved relative to triceps in neurological conditions, but biceps has a larger cortical representation and might be expected to show preferential weakness in ALS. Methods: Using the South-East England Register for Amyotrophic Lateral Sclerosis, we performed a retrospective longitudinal cohort study and extracted the modified Medical Research Council (MRC) muscle strength score for biceps and triceps in patients with a diagnosis of upper limb-onset ALS in the 19-year period 1996–2015. A Wilcoxon signed-rank test was used to assess the relative strength of the muscles within the total sum of the upper limbs involved in the study. Results: There were 659 people with upper limb onset of weakness. In 215 there were insufficient data to perform the analysis, and a further 33 were excluded for other reasons, leaving 411 for analysis. Biceps was stronger than triceps in 87 limbs, and triceps was stronger than biceps in 258 limbs, with no difference seen in the remaining 477. Triceps strength scores (mean rank=186.1) were higher than ipsilateral biceps strength scores (mean rank=134.2), Z=−10.1, p<0.001 (two-tailed). Conclusion: Triceps strength is relatively preserved compared with biceps in ALS. This is consistent with a broadly corticofugal hypothesis of selective vulnerability, in which susceptibility might be associated with larger cortical representation.